STUDI PERMEABILITAS TERHADAP TANAH LEMPUNG YANG DICAMPUR DENGAN MATERIAL LAIN - M., SUDARMANTO.
The study on permeability by compacting and adding additive to soils is seldom very conducted . This research attemptgd to reveal the behavior of the permeability of soils which was compacted at optimum water content and mixed with cement and chemical agants. The result showed that by mixing the soil with cement, cement + Na2CO3, cement + KOH and special chemical solution (RRP 2-3- 5 Special), the permeability of soils (especially Bandung clay) was reduced up to between 0.01 up to 0.001 . The mixing materials (cement, Na2CO3, KOH, RRP 2-3-5 Special) was able to change the physical characteristic of soils and it was also presumed that the structure of soils was altered. It also implion on the decreasing the void ratio. In this research the method for testing permeability proposed by ASTM and AASHTO was used. The concentration variation of the mixing materials were soil + 5% cement, soil + 5% cement + Na2CO3, soil + 10% cement + KOH, soil + 10% cement + Na2CO3 and soil + RRP 2-3-5 Special. The concentration of Na2CO3 and KOH were 1 gmol/l which were mixed ' to the soils of 2% of its dry weight. The concentration of RRP 2-3-5 Special was made by dissolving 3 grams RRP 2-3-5 Special in 350 cc, 475 cc and 600 cc of water. The solution then used to 0.3 cubic meter of soils. The equipment used in this research was a constant pressure system connected to oedometer cell. This system could give a maximum pressure up to 200 kN/m2. From a series of tests conducted to Bandung clay mixed with 5% cement, 5% cement + chemicals and RRP, it showed that soils collected from two locations out of three were more effective.